2012
DOI: 10.1007/s00382-012-1291-6
|View full text |Cite
|
Sign up to set email alerts
|

A multi-data set comparison of the vertical structure of temperature variability and change over the Arctic during the past 100 years

Abstract: A multi-data set comparison of the vertical structure of temperature variability and change over the Arctic during the past 100 yearsBrönnimann, S; Grant, A N; Compo, G P; Ewen, T; Griesser, T; Fischer, A M; Schraner, M; Stickler, A Abstract: We compare the daily, interannual, and decadal variability and trends in the thermal structure of the Arctic troposphere using eight observation-based, vertically resolved data sets, four of which have data prior to 1948. Comparisons on the daily scale between historical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…The largest uncertainties associated with this database identified in Polar Regions as well as in the stratospheric layers. In general 20CR data has lower level of accuracy for the period until 1940s (Brönnimann et al 2012;Paek, Huang 2012).…”
Section: Methodsmentioning
confidence: 97%
“…The largest uncertainties associated with this database identified in Polar Regions as well as in the stratospheric layers. In general 20CR data has lower level of accuracy for the period until 1940s (Brönnimann et al 2012;Paek, Huang 2012).…”
Section: Methodsmentioning
confidence: 97%
“…In 20CR regions with temperature reductions are more pronounced than in the other two data sets -in particular, large differences are found in the NH and SH polar regions. For 20CR it is known that the Arctic temperature field suffers from a large, time-varying bias (Brönnimann et al, 2012) and an incorrect sea-ice distribution (Compo et al, 2011). However, HadCRUT4 and GIS-TEMP are also affected by a very low spatial and temporal coverage of instrument-based observations in these regions.…”
Section: Temperature Trends After 1850mentioning
confidence: 99%
“…Both components, the atmosphere and the ocean, are coupled every 24 h using the OA-SIS3 coupler (Budich et al, 2010;Valcke, 2013). At the beginning of each model day the coupler exchanges momentum, heat, freshwater fluxes, as well as information on the SSTs, sea-ice extent, and snow cover on sea ice between the atmosphere and the ocean.…”
Section: Mpiommentioning
confidence: 99%
“…This is in agreement with the findings presented by Paek and Huang (2012) who showed the total absence of the QBO in the 20CR series over the tropical stratosphere. Brönnimann et al (2012) demonstrated inconsistencies in the variability of the 20CR series within the stratosphere too. Taking into account this lack of realistic representation of the major stratospheric phenomena, the 20CR dataset should be considered as unsuitable for stratospheric studies.…”
Section: Utilized Datasets and Concluding Remarksmentioning
confidence: 93%